Natural additives for poly (hydroxybutyrate-co-hydroxyvalerate)-phbv: Effect on mechanical properties and biodegradation - Brunel D.G. (2014)
© 2014.In this work, the improvement of mechanical properties in biodegradable materials was obtained through the incorporation of natural and also biodegradable plasticizers and nucleation agents into the PHBV copolymer. PHBV production with different quantities of additives was obtained by extrusion followed by injection. The additives in the copolymer were efficient, resulting in an adequate processing due to the presence of nucleate and an improvement of the mechanical properties of the resulting material provided by the action of the plasticizer. The formulation with the minimum amount of additive content, 5% epoxidized cottonseed oil and 0.1% Licowax, was the most effective showing 35% reduction in the elastic modulus, and 18% in the PHBV crystallinity; 58% increase in impact resistance and 46% increase in elongation. Furthermore, it is important to emphasize that the natural additives were very efficient for biodegradation, showing a mass loss higher of pure PHBV.